A EVOLUÇÃO DO MARKETING POLÍTICO NA TELEVISÃO BRASILEIRA: 1989 2002. - Makovics, Nahara Cristine (2007)
This thesis will analyze political campaigns, specifically, on the programs that were transmitted in Brazilian broadcasting from 1989 to 2002. We will expose about the highlights of these political campaigns during these periods, however, the focus will be on 2002 Brazilian elections. The present research will discuss important points such as image projection of the runners of the Federative Republic of Brazil, communication, the trajectory, the television as tool of mass communication, political propaganda, electoral advertising, political marketing, in a general way, the tools used to reach the power.(AU)